Telegram as a Battlefield: Kremlin-Related Communications During the Russia-Ukraine Conflict - Bawa, Apaar; Kursuncu, Ugur; Achilov, Dilshod; Shalin, Valerie L.; Agarwal, Nitin; Akbas, Esra (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
Telegram emerged as a crucial platform for both parties during the conflict between Russia and Ukraine. Per its minimal policies for content moderation, Pro-Kremlin narratives and potential misinformation were spread on Telegram, while anti-Kremlin narratives with related content were also propagated, such as war footage, troop movements, maps of bomb shelters, and air raid warnings. This paper presents a dataset of posts from both pro-Kremlin and anti-Kremlin Telegram channels, collected over a period spanning a year before and a year after the Russian invasion. The dataset comprises 404 pro-Kremlin channels with 4,109,645 posts and 114 anti-Kremlin channels with 1,117,768 posts. We provide details on the data collection process, processing methods, and dataset characterization. Lastly, we discuss the potential research opportunities this dataset may enable researchers across various disciplines.